Crime in Baghdad community and methods of combating it in (The Book of EVENTS by an anonymous author of the eighth century AH) 626-700 AH / 1229-1300AD - AL MAFRACHI , HADI HUSSEIN MOHSIN (International Journal of Psychosocial Rehabilitation, 2020)
So many often, Muslim historians are being accused of dedicating their works to only political and military affairs of the Islamic community and neglecting other social and anthropological aspects. Another aspect is the widely spread misconception which was taken as a non-negotiable fact that Iraq was severely detreated after the Mongol-Ilkhan occupation in 656 AH / 1258AD. This study has concluded that ((The Book of EVENTS by an anonymous author of the eighth century AH)) had categorically denied the accusation leveled against Muslim historians by monitoring and reporting a large variety of law-breaking incidents and individual and organized crimes in Baghdad. The book scrutinized the motives and urges behind these crimes. It also clearly manifested the methods of investigation and interrogation of the accused along with a comprehensive explanation of the types of penalties and judicial rulings imposed on criminals, and local authorities’ highly professional and rapid efforts to combat crime, as well as giving demonstration of effective interaction Baghdad community groups in fighting crimes. Another outcome of this study is the fact that security establishments and people in charge of them at that time were highly ranked professional.